Cadre deployment and implications for ethical public administration in Madibeng Local Municipality - Mothibi, Yvonne (University of the Witwatersrand, Johannesburg, 2024)
The thesis rests on the argument that the implementation of cadre deployment in South Africa’s public sector, intended to promote representativeness and transformation, has inadvertently led to ethical dilemmas and governance challenges, undermining the principles of transparency, accountability, and meritocracy. The study investigates the ethical and governance implications of cadre deployment within South Africa’s public sector, focusing on the case study of Madibeng Local Municipality in the North West province of South Africa. The main aim is to understand how the practice of cadre deployment, intended to ensure representativeness and transform the post-apartheid landscape, has paradoxically fostered ethical dilemmas and governance challenges, undermining the constitutional principles of transparency, accountability, and meritocracy. The study is underpinned by an interpretivist methodology, employing semi-structured interviews and document analysis to capture the nuanced experiences and perceptions of municipal officials, political leaders, and community members. This approach facilitates a deep, contextual understanding of the complex dynamics surrounding cadre deployment and its intersection with ethical public administration. The theoretical and conceptual framework underpinning the study triangulates postcolonial theory, critical governance studies, and decolonial ethics to analyse the persistence of colonial legacies in contemporary governance practices and the ethical considerations therein. This framework provides a comprehensive lens to examine the multifaceted effects of cadre deployment on ethical governance within a post-apartheid context, particularly in the unique socio-political environment of the Madibeng Municipality. The findings suggest that cadre deployment, while aimed at redressing historical injustices, has led to an erosion of ethical standards and governance quality, manifested in nepotism, favouritism, and compromised service delivery. These outcomes challenge the transformative goals of the policy, indicating a significant misalignment between its intended objectives and actual impacts on public administration. The study contributes to the discourse on public sector ethics and governance in post-apartheid South Africa by providing empirical evidence of the unintended consequences of cadre deployment in local governance.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cadre Deployment; Ethical Public Administration; SDG-11: Sustainable cities and communities